(2m+n)(2m-n)+n(2m+n)-8m^2n^3/(2n^3) m=-2分之1,n=2013
1个回答
原式=(2m+n)(2m-n+n)-4m^2
=2m(2m+n)-4m^2
=4m^2+2mn-4m^2
=2mn
=2*(-1/2)*2013
=-2013
相关问题
已知2m+n分之m-2n=3,则2m+n分之3(m-2n)+3(2m+n)分之m-2n-4(2m+n)分之5(m-2n)
已知2m+n分之m-2n=3,求代数式2m+n分之3m-6n减3(2m+n)分之m-2n-m-2n分之5(2m+n)
|m+2n分之2m-n|=3,求m+2n分之2(2m-n)-m+2n分之2m-n-3的值?
m+2n分之2m-n的绝对值=3,求m+2n分之2(2m-n)-m+2n分之2m-n-3
m+2n分之2m-n的绝对值=3,求m+2n分之2(2m-n)-m+2n分之2m-n-3的值
1/m-n,2/n^2-m^2,3n/2(m+n)通分
计算1/(m-n)-1/(m+n)-2n/(m^2+n^2)-4n^3/(m^4+n^4)-8n^7/(m^8+n^8)
计算1/(m-n)-1/(m+n)-2n/(m^2+n^2)-4n^3/(m^4+n^4)-8n^7/(m^8+n^8)
当2m+n分之2m-n=3时,则代数式2(2m-n)分之3(2m+n)减去3(2m+n)分之2(2m-n)的值是多少?(
若(m-2n)/(2m+n)=3,则[3(m-2n)/(2m+n)-(m-2n)/[2(2m+n)] - {9(m-2n